Selected Bibliography of Completed Theses and Dissertations Related to North Carolina Subjects. (North Carolina Historical Review, 2025)
The document is a selected bibliography of completed theses and dissertations related to North Carolina subjects, compiled by Kathryn McKee. It includes entries from various fields such as African American Studies, Anthropology and Archaeology, Education, Environmental Studies, Historic Sites and Museums, History, Latino/a Studies, Music, Native American Studies, Parks, Recreation, and Tourism, Political Science, Public Policy, Religion, and Sociology. The entries list the author, title of the thesis or dissertation, type of degree, university granting the degree, year of award, and number of pages.